2018
DOI: 10.1038/s41435-018-0024-1
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila is permissive to arthritis in the K/BxN mouse model of arthritis

Abstract: Studies have identified abnormalities in the microbiota of patients with arthritis. To evaluate the pathogenicity of human microbiota, we performed fecal microbial transplantation from children with spondyloarthritis and controls to germ-free KRN/B6xNOD mice. Ankle swelling was equivalent in those that received patient vs control microbiota. Principal coordinates analysis revealed incomplete uptake of the human microbiota with over-representation of two genera (Bacteroides and Akkermansia) among the transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 24 publications
(35 reference statements)
2
21
0
Order By: Relevance
“…Assessing the effect of random sampling at various N, and also as N accumulated, we were able to illustrate that pairwise trio-trio comparisons between the simulated datasets almost always produce non-significant results when iterative trios were compared (due to large SD overlapping; see bars in Figure 1D representing 21 sets of pairwise trio-trio p-values). However, as N increases by the cumulative addition of all (mostly ‘non-significant’) donor trios ( i.e ., N increases in multiples of 3, for a range of N between 3 and 63 donors/group; [3, 6, 9, 12…63]), pairwise statistical comparisons between the simulated datasets did not produce consistent results (see line plots in Figure 1D representing p-value for cumulative addition of donors when sampling iterations were simulated).…”
Section: Resultsmentioning
confidence: 99%
“…Assessing the effect of random sampling at various N, and also as N accumulated, we were able to illustrate that pairwise trio-trio comparisons between the simulated datasets almost always produce non-significant results when iterative trios were compared (due to large SD overlapping; see bars in Figure 1D representing 21 sets of pairwise trio-trio p-values). However, as N increases by the cumulative addition of all (mostly ‘non-significant’) donor trios ( i.e ., N increases in multiples of 3, for a range of N between 3 and 63 donors/group; [3, 6, 9, 12…63]), pairwise statistical comparisons between the simulated datasets did not produce consistent results (see line plots in Figure 1D representing p-value for cumulative addition of donors when sampling iterations were simulated).…”
Section: Resultsmentioning
confidence: 99%
“…Asquith and colleagues reported increased cecal abundance of A muciniphila in HLA‐B27‐transgenic rats corresponding to onset of intestinal inflammation and arthritis . Finally, Stoll demonstrated that while monocolonization of A muciniphila in an arthritis model did not result in a demonstrable increase in arthritis severity, the addition of this organism to an otherwise normal microbiota obtained from a healthy child did increase arthritis severity accompanied by diminished intestinal mucin content.…”
Section: Microbiota Alterations In Jiamentioning
confidence: 98%
“…In contrast, in the world of inflammatory diseases, there are not for the most part “good guys” or “bad guys.” Rather, the impact of a specific organism is likely to depend on the age of exposure, other community members, host genetics, the host's immune response against the organism, and myriads of other factors. Thus, species that emerge as pathogenic in one condition (eg, Prevotella and RA may be reduced in another; pediatric exposure to Bacteroides may predispose to JIA while adult exposure may be protective; and mucin‐degrading organisms such as A muciniphila and Ruminococcus may be harmless in isolation but harmful in the right setting . Furthermore, many of the organisms identified as potentially relevant to JIA pathogenesis may be beneficial for other reasons, and their obliteration even if technically possible may have downstream effects that would need to be monitored.…”
Section: Therapeutic Potential Of Microbial Alterationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have started to see tantalizing hints of answers to these tough questions, including studies on the pathogenic role of Akkermansia mucinophila in juvenile spondyloarthritis and the potential benefits of elemental formula in children with active JIA . Still, these are early days of microbiome research in JIA, and causal interpretations of the published evidence would be premature.…”
mentioning
confidence: 99%